Cadherin-mediated differential cell adhesion controls slow muscle cell migration in the developing zebrafish myotome - Cortés, Fernando; Daggett, David; Bryson-Richardson, Robert J; Neyt, Christine; Maule, John; Gautier, Phillipe; Hollway, Georgina E; Keenan, David; Currie, Peter D (Developmental cell, 2003)
Slow-twitch muscle fibers of the zebrafish myotome undergo a unique set of morphogenetic cell movements. During embryogenesis, slow-twitch muscle derives from the adaxial cells, a layer of paraxial mesoderm that differentiates medially within the myotome, immediately adjacent to the notochord. Subsequently, slow-twitch muscle cells migrate through the entire myotome, coming to lie at its most lateral surface. Here we examine the cellular and molecular basis for slow-twitch muscle cell migration. We show that slow-twitch muscle cell morphogenesis is marked by behaviors typical of cells influenced by differential cell adhesion. Dynamic and reciprocal waves of N-cadherin and M-cadherin expression within the myotome, which correlate precisely with cell migration, generate differential adhesive environments that drive slow-twitch muscle cell migration through the myotome. Removing or altering the expression of either protein within the myotome perturbs migration. These results provide a definitive example of homophilic cell adhesion shaping cellular behavior during vertebrate development.